Resourceful Fast Discrete Hartley Transform to Replace Discrete Fourier Transform with Implementation of DHT Algorithm for VLSI Architecture (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Discrete Fourier Transform (DFT) is used in a range of digital signal processing applications, such as signal and image compression systems, filter banks, signal representation or harmonic analysis. The Discrete Hartley Transform (DHT) can be used to effectively replace the DFT when the input sequence is real. This paper introduces and applies the Discrete Hartley Transform (DHT) algorithm, which is well suited to the VLSI architecture. The purpose of using the DHT algorithm is to reduce the complexity of the VLSI architecture. With the introduction of VLSI architectures, 100,000 transistors can be mounted on a single chip. For manufacturers, the verification of these circuits on breadboards is not feasible. Computer-aided design methods have now come into being, but programmers also had to make connections manually at the gate level. Subsequently, Hardware Description Language (HDL) such as Verilog and VHDL came into being. With the integration of the DHT algorithm and its execution, Verilog authors have worked to reduce the complexity of the VLSI circuits in this article. With reduced complexity, the power consumption is reduced and thus the area is therefore reduced. DHT is an algorithm for the Radix-2. It is especially useful for image and signal processing. The DHT algorithm for length N=8 is introduced here.